Laser color converter preparation method and laser color converter structure
By using a high thermal conductivity fluorescent glass layer and thermal conductivity groove structure in the laser color converter, the problem of poor thermal stability in traditional color converters under high power lasers is solved, and higher luminous brightness and reliability are achieved.
Patent Information
- Application Number
- CN202510305320.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-14
AI Technical Summary
Traditional resin-based phosphor color converters have thermal corrosion and carbonization problems under high power density laser excitation, which cannot meet the practical application of laser illumination.
By using the laser color converter preparation method, a laser color converter structure with high thermal conductivity and thermal stability is formed by making grooves on the heat dissipation substrate and filling it with excess fluorescent glass slurry.
It effectively avoids the problem of depression in the groove caused by glass fusion and organic matter volatilization in the fluorescent slurry, improves the thermal stability and luminous brightness of the laser color converter, and extends the reliability of the white laser light source.
Smart Images

Figure CN119844732A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor lighting, and relates to a laser color converter preparation method and a laser color converter structure. Background Art
[0002] With the continuous increase in global energy consumption and the increasing pressure on environmental protection, the demand for energy-saving and efficient lighting technology has gradually become one of the core issues of social development. As an emerging light source technology, semiconductor lighting has attracted widespread attention in the lighting field due to its high efficiency, energy saving, and strong directionality. Compared with traditional light sources, semiconductor lighting has significant advantages in energy saving, life, environmental protection, flexibility, durability and other aspects, and has gradually replaced traditional incandescent lamps and fluorescent lamps to become the mainstream lighting choice. The new generation of green laser lighting is widely penetrating into urban lighting, automobiles, industry, medical care, display, commerce and other fields with its high efficiency, long life, low energy consumption and strong controllability. With the continuous advancement of technology, laser lighting will bring energy-saving, environmental protection, innovative design and high-quality experience solutions to more fields in the future.
[0003] With the demand for high-power and high-density lighting solutions, multi-chip packaging integrated blue light emitting diode technology (LED) and blue laser diode (LD) have emerged. Compared with blue light emitting diodes (LED), blue LD has the advantages of low beam divergence, long irradiation distance, no efficiency reduction, and high output power density.
[0004] Blue LD can achieve high brightness lighting by simply increasing the input power density, but the large amount of heat accumulation and light conversion loss caused by high-power density laser excitation bring new challenges to the thermal management of light color converters. Traditional resin-based phosphor (PiS) color converters have poor thermal stability and limited thermal conductivity, and have serious thermal corrosion and carbonization problems under high-power density laser excitation, which cannot meet the practical application of laser lighting. Therefore, new color converters with different structural configurations and material designs are urgently needed to be developed.
[0005] To this end, researchers have proposed inorganic fluorescent conversion materials (luminescent single crystals, fluorescent ceramics, fluorescent glass, etc.) for white light LD packaging. Fluorescent conversion materials are a key link in laser fluorescence technology. Different from the organic fluorescent conversion materials commonly used in white light LEDs, due to the high light power density and small radiation spot of blue light LD, coupled with the heat generated by non-radiative transitions during the fluorescence conversion process, local high temperatures will be generated in the laser irradiation area, while traditional organic fluorescent conversion materials have low thermal conductivity and are prone to yellowing and carbonization at high temperatures, which leads to the failure of fluorescent materials. Fluorescent glass is an inorganic composite material composed of glass and phosphors, which has the advantages of simple preparation process, adjustable luminescent properties, low cost, and easy batch production. However, existing fluorescent glass has the disadvantages of low thermal conductivity and poor thermal stability, which makes it difficult to meet the needs of high power density laser driving or excitation, resulting in luminescent saturation problems in white light LDs, limiting the development of laser lighting and display technology. Summary of the invention
[0006] In view of this, an object of the present invention is to provide a method for preparing a laser color converter and a laser color converter structure to solve the problems raised by the above-mentioned background technology.
[0007] The present invention is implemented by the following scheme: A method for preparing a laser color converter comprises the following steps: S1. Making grooves on the heat dissipation substrate by machining, laser processing or etching; S2, filling the groove of the heat dissipation substrate with excess fluorescent glass slurry, the portion of the excess fluorescent glass slurry exceeding the bearing area of the groove falls on the heat dissipation substrate, and coating the glass slurry on the surface of the heat dissipation cover plate; S3, performing the first high-temperature sintering on the heat dissipation substrate filled with an excess of fluorescent glass slurry and the heat dissipation cover plate coated with glass slurry; S4, grinding the excess fluorescent glass layer produced after sintering on the heat dissipation substrate until the fluorescent glass just fills the groove and is flush with the surface of the heat dissipation substrate; S5. Align and bond the bonding layer formed by sintering the glass slurry on the heat dissipation cover plate with the surface of the heat dissipation substrate with the fluorescent glass, and perform a second high-temperature sintering to form a laser color converter.
[0008] Furthermore, the thickness of the laser color converter is 1-5 mm; the depth of the groove is 100 μm-500 μm; the area of the groove is 30%-90% of the surface area of the heat dissipation substrate; and the thickness of the adhesive layer (3) is 30 μm-350 μm.
[0009] Furthermore, the fluorescent glass paste is formed by mixing fluorescent powder, low-temperature glass powder and organic solvent, and the amount of fluorescent powder is 20%-300% of the weight of the low-temperature glass powder; the glass paste is formed by mixing low-temperature glass powder and organic solvent.
[0010] Furthermore, the sintering temperature of the fluorescent glass paste is greater than 600°C, and the glass transition temperature of the low-temperature glass powder is lower than 500°C.
[0011] Furthermore, the sintering temperature of the fluorescent glass paste and the glass paste is 620° C. to 700° C., and the sintering time is 30 to 60 minutes.
[0012] Furthermore, the heat dissipation substrate material is made of one or more composite materials selected from ceramics, metals or glass; and the heat dissipation cover plate is made of high thermal conductivity heat dissipation alumina or diamond.
[0013] Furthermore, the fluorescent glass slurry fills 200% of the volume of the groove.
[0014] Furthermore, during the second high-temperature sintering, pressure is applied to the heat dissipation cover plate surface to achieve pressure sintering.
[0015] A laser color converter structure: the laser color converter includes a heat dissipation substrate, a fluorescent glass layer, an adhesive layer and a heat dissipation cover plate, the fluorescent glass layer is arranged on the upper surface of the heat dissipation substrate, the adhesive layer covers the upper surface of the combination of the heat dissipation substrate and the fluorescent glass layer, and the heat dissipation cover plate is arranged on the adhesive layer.
[0016] Furthermore, a groove is provided on the upper surface of the heat dissipation substrate, the fluorescent glass layer is filled in the groove, and the thickness of the fluorescent glass layer is the same as the depth of the groove.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. By filling the heat dissipation substrate with excessive fluorescent glass slurry, it is possible to effectively avoid the inevitable depression inside the groove due to the glass fusion and volatilization of organic matter in the fluorescent slurry, that is, to avoid the presence of concave space in the groove after sintering; 2. The heat dissipation cover plate coated with glass paste on the surface is sintered for the first time instead of being directly coated on the processed heat dissipation substrate with fluorescent glass layer. On the one hand, because when the glass paste is sintered, it may also produce depressions due to the volatilization of organic matter, so the bonding layer sintered once needs to be polished and trimmed first; on the other hand, if the glass paste is directly coated on the processed heat dissipation substrate with fluorescent glass layer, the depression of the fluorescent glass layer that may have the depression problem will be filled with glass paste, so that the depression of the fluorescent glass layer sintered twice will produce defects such as pores due to the volatilization of organic matter in the glass paste, which affects the performance of the product, that is, the problem of depressions, pores and other defects in the bonding layer is solved; 3. The heat-conducting groove structure is used to improve the heat dissipation performance of the laser color converter, avoid the problem of luminous saturation, and effectively improve the luminous brightness and thermal stability of the white laser light source; no organic adhesive material is used in the laser color converter, which avoids the failure or even carbonization of the organic adhesive material at high temperature, and improves the long-term reliability of the white laser light source; 4. The laser color converter is mainly used for high-brightness fluorescence conversion white laser light source. It can withstand high-power density laser drive or excitation, so that the white laser light engine and its equipment have ultra-high brightness and reliability, promoting the development of laser lighting and display technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the process flow of the preparation method of an embodiment of the present invention; Figure 2 is a schematic diagram of a reflective layer according to an embodiment of the present invention; Figure 3 It is a schematic structural diagram of an embodiment of the present invention.
[0019] In the figure: 1-heat sink substrate; 2-fluorescent glass layer; 30-containing YAG yellow phosphor; 31-glass matrix; 3-adhesive layer; 4-heat sink cover; 5-groove; 6-heat sink cover surface; 7-heat sink substrate surface; 8-heat sink cover surface. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0021] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0022] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0023] like Figure 1-3 As shown, a method for preparing a laser color converter includes the following steps: S1. Making grooves on the heat dissipation substrate by machining, laser processing or etching; S2, filling the groove of the heat dissipation substrate with excess fluorescent glass slurry, the portion of the excess fluorescent glass slurry exceeding the bearing area of the groove falls on the heat dissipation substrate, and coating the glass slurry on the surface of the heat dissipation cover plate; S3, performing the first high-temperature sintering on the heat dissipation substrate filled with an excess of fluorescent glass slurry and the heat dissipation cover plate coated with glass slurry; S4, grinding the excess fluorescent glass layer produced after sintering on the heat dissipation substrate until the fluorescent glass just fills the groove and is flush with the surface of the heat dissipation substrate; S5. Align and bond the bonding layer formed by sintering the glass slurry on the heat dissipation cover plate with the surface of the heat dissipation substrate with the fluorescent glass, and perform a second high-temperature sintering to form a laser color converter.
[0024] In this embodiment, a more specific preparation method is: Step 1: Use Al2O3 with a thickness of 1 mm as the heat dissipation substrate, and machine a groove with a depth of 100 μm on the heat dissipation substrate. Use sapphire with a thickness of 1 mm as the heat dissipation cover; Step 2: Mix 0.35g of pineol and 0.017g of ethyl cellulose, and stir ultrasonically at 80°C until the ethyl cellulose is completely dissolved, as a bottle of organic solvent. Repeat the above operation to obtain another bottle of organic solvent, add 0.8g of YAG yellow phosphor and 0.5g of low-temperature borosilicate glass powder to one bottle, and add 0.5g of low-temperature borosilicate glass powder to another bottle. Finally, magnetic stirring is performed for 15 minutes to obtain fluorescent glass slurry and glass slurry. The fluorescent glass slurry is formed by combining the glass matrix of the glass slurry and the phosphor; respectively apply an excess of fluorescent glass slurry on the heat dissipation substrate obtained in step 1, and apply the glass slurry on the heat dissipation cover plate, and place them at 110°C for drying for 30 minutes; then place the two in a high-temperature furnace and sinter at 620°C for 30 minutes to obtain a heat dissipation substrate with a fluorescent glass layer, the thickness of the fluorescent glass layer is about 200μm, and a heat dissipation cover plate with a glass layer, the thickness of the glass layer is about 30μm. ~150μm, of course, the heat dissipation cover can be coated with excess glass slurry and then polished to the actual required size.
[0025] Step three, grinding is performed on the heat dissipation substrate with the fluorescent glass layer obtained in step two to obtain a composite structure with a fluorescent glass layer thickness of about 100 μm, that is, the excess fluorescent glass after sintering is ground until it just fills the groove and is flush with the surface of the heat dissipation substrate, so as to achieve the purpose of consistency between the thickness of the fluorescent glass and the depth of the groove.
[0026] Step 4: Align and bond the bonding layer formed by sintering the glass slurry on the heat dissipation cover plate with the surface of the heat dissipation substrate with the fluorescent glass, place the entire structure in a high-temperature furnace, and sinter under pressure at 620°C for 60 minutes to achieve fixation between the heat dissipation substrate and the heat dissipation cover plate to form a laser color converter.
[0027] In this embodiment, by filling the heat dissipation substrate with excessive fluorescent glass slurry, it is possible to effectively avoid the inevitable depression inside the groove due to the glass fusion and volatilization of organic matter in the fluorescent slurry, that is, to avoid the presence of depression space in the groove after sintering. At the same time, the heat dissipation cover plate coated with glass slurry on the surface is also sintered for the first time, instead of being directly applied to the processed heat dissipation substrate with a fluorescent glass layer. On the one hand, because depressions may also be generated due to the volatilization of organic matter when the glass slurry is sintered, it is necessary to first grind and trim the bonding layer sintered once; on the other hand, if the glass slurry is directly applied to the processed heat dissipation substrate with a fluorescent glass layer, the depression of the fluorescent glass layer that may have a depression problem will be filled with glass slurry, so that the depression of the fluorescent glass layer sintered for the second time will produce defects such as pores due to the volatilization of organic matter in the glass slurry, affecting the performance of the product.
[0028] In this embodiment, the thickness of the laser color converter is 1-5 mm; the depth of the groove is 100 μm-500 μm; the area of the groove is 30%-90% of the surface area of the heat dissipation substrate, and the thickness of the adhesive layer (3) is 30 μm-350 μm.
[0029] In this embodiment, the fluorescent glass paste is formed by mixing fluorescent powder, low-temperature glass powder and organic solvent, and the amount of fluorescent powder is 20%-300% of the weight of the low-temperature glass powder; the glass paste is formed by mixing low-temperature glass powder and organic solvent.
[0030] In this embodiment, specifically: the heat sink substrate is made of Al2O3, the phosphor contains YAG yellow phosphor, the heat sink substrate and the heat sink cover plate can be 1 mm thick, the fluorescent glass layer is 100 μm, and the radius of the fluorescent glass layer is 5 mm.
[0031] In this embodiment, the sintering temperature of the fluorescent glass paste is greater than 600°C, and the glass transition temperature of the low-temperature glass powder is lower than 500°C.
[0032] In this embodiment, the sintering temperature of the fluorescent glass paste and the glass paste is 620° C. to 700° C., and the sintering time is 30 to 60 minutes.
[0033] In this embodiment, the heat dissipation substrate material is made of one or more composite materials selected from ceramics, metals or glass; the heat dissipation cover plate is made of high thermal conductivity heat dissipation alumina or diamond.
[0034] In this embodiment, the filling amount of the fluorescent glass slurry is 200% of the volume of the groove.
[0035] In this embodiment, during the second high-temperature sintering, pressure is applied to the heat dissipation cover plate surface to achieve pressure sintering, which can better ensure that the bonding layer bonds the heat dissipation substrate and the heat dissipation cover plate.
[0036] A laser color converter structure made by the above preparation method: the laser color converter includes a heat dissipation substrate, a fluorescent glass layer, an adhesive layer and a heat dissipation cover plate, the fluorescent glass layer is arranged in the upper surface of the heat dissipation substrate, the adhesive layer covers the upper surface of the combination of the heat dissipation substrate and the fluorescent glass layer, the heat dissipation cover plate is arranged on the adhesive layer, the heat dissipation cover plate and the heat dissipation substrate are fixed by the adhesive layer and kept flat, and the adhesive layer completely covers the fluorescent glass layer and the surface of the heat dissipation substrate and keeps them flat.
[0037] In this embodiment, a groove is opened on the upper surface of the heat dissipation substrate, and the fluorescent glass layer is filled in the groove. The thickness of the fluorescent glass layer is the same as the depth of the groove.
[0038] In this embodiment, the laser color converter structure is used for a high light efficiency phosphor-converted white laser light source.
[0039] In this embodiment, in summary, the present invention discloses a method for preparing a laser color converter and a laser color converter structure, which is a reflective structure. Its structure includes a heat dissipation substrate, a heat dissipation cover plate, a fluorescent glass layer and an adhesive layer. The heat dissipation substrate is processed with a groove, the fluorescent glass layer is filled in the groove, and the heat dissipation cover plate and the heat dissipation substrate are fixed by an adhesive layer. The heat dissipation substrate is made of Al2O3 and the heat dissipation cover plate is made of sapphire. At the same time, the present invention discloses a method for preparing a high thermal conductivity fluorescent glass sheet. The laser color converter structure is mainly used for high-brightness fluorescent conversion white laser light sources, which can withstand high-power density laser drive or excitation, so that the white laser light engine and its equipment have ultra-high brightness and reliability, and promote the development of laser lighting and display technology.
[0040] Unless otherwise stated, any technical solution disclosed in the present invention disclosed above, if it discloses a numerical range, then the disclosed numerical range is a preferred numerical range, and any technician in the field should understand that the preferred numerical range is only a numerical value with a more obvious technical effect or representative value among many implementable numerical values. Since there are too many numerical values to be exhaustive, the present invention discloses some numerical values to illustrate the technical solution of the present invention, and the numerical values listed above should not constitute a limitation on the scope of protection of the present invention.
[0041] If the words "first", "second" and so on are used in this article to limit components, those skilled in the art should know that the use of "first" and "second" is only for the convenience of description to distinguish the components. Unless otherwise stated, the above words have no special meaning.
[0042] If the present invention discloses or involves components or structures that are fixedly connected to each other, then, unless otherwise stated, the fixed connection can be understood as: a detachable fixed connection (for example, connection using bolts or screws), and can also be understood as: a non-detachable fixed connection (for example, riveting, welding). Of course, the mutual fixed connection can also be replaced by an integrated structure (for example, manufactured by integrated molding using a casting process) (except when it is obviously impossible to use an integrated molding process).
[0043] In addition, the orientations or positional relationships indicated by terms such as "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", and "outside" used in any of the technical solutions disclosed in the above-mentioned invention are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing this patent, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on this patent. Unless otherwise stated, the terms used to indicate shapes used in any of the technical solutions disclosed in the above-mentioned invention include shapes that are approximate, similar, or close to them.
[0044] Any component provided by the present invention may be assembled from a plurality of separate components, or may be a separate component manufactured by an integral forming process.
[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A method for preparing a laser color converter, characterized in that: The steps include: S1. Making grooves on the heat dissipation substrate by machining, laser processing or etching; S2, filling the groove of the heat dissipation substrate with excess fluorescent glass slurry, the portion of the excess fluorescent glass slurry exceeding the bearing area of the groove falls on the heat dissipation substrate, and coating the glass slurry on the surface of the heat dissipation cover plate; S3, performing the first high-temperature sintering on the heat dissipation substrate filled with an excess of fluorescent glass slurry and the heat dissipation cover plate coated with glass slurry; S4, grinding the excess fluorescent glass layer produced after sintering on the heat dissipation substrate until the fluorescent glass just fills the groove and is flush with the surface of the heat dissipation substrate; S5. Align and bond the bonding layer formed by sintering the glass slurry on the heat dissipation cover plate with the surface of the heat dissipation substrate with the fluorescent glass, and perform a second high-temperature sintering to form a laser color converter.
2. The method for preparing a laser color converter according to claim 1, characterized in that: The thickness of the laser color converter is 1-5 mm; the depth of the groove is 100 μm-500 μm; the area of the groove is 30%-90% of the surface area of the heat dissipation substrate; and the thickness of the adhesive layer (3) is 30 μm-350 μm.
3. The method for preparing a laser color converter according to claim 1, characterized in that: The fluorescent glass paste is formed by mixing fluorescent powder, low-temperature glass powder and organic solvent, and the amount of fluorescent powder is 20%-300% of the weight of the low-temperature glass powder; the glass paste is formed by mixing low-temperature glass powder and organic solvent.
4. The method for preparing a laser color converter according to claim 3, characterized in that: The sintering temperature of the fluorescent glass paste is greater than 600°C, and the glass transition temperature of the low-temperature glass powder is lower than 500°C.
5. The method for preparing a laser color converter according to claim 4, characterized in that: The sintering temperature of the fluorescent glass paste and the glass paste is 620° C. to 700° C., and the sintering time is 30 to 60 minutes.
6. The method for preparing a laser color converter according to claim 1, characterized in that: The heat dissipation substrate material is made of one or more composite materials selected from ceramics, metals or glass; the heat dissipation cover plate is made of high thermal conductivity heat dissipation alumina or diamond.
7. The method for preparing a laser color converter according to claim 1, characterized in that: The filling amount of the fluorescent glass slurry is 200% of the volume of the groove.
8. The method for preparing a laser color converter according to claim 1, characterized in that; During the second high-temperature sintering, pressure is applied to the heat dissipation cover plate surface to achieve pressure sintering.
9. A laser color converter structure, manufactured by the laser color converter manufacturing method according to claim 1, characterized in that: The laser color converter includes a heat dissipation substrate, a fluorescent glass layer, an adhesive layer and a heat dissipation cover plate, wherein the fluorescent glass layer is arranged on the upper surface of the heat dissipation substrate, the adhesive layer covers the upper surface of the combination of the heat dissipation substrate and the fluorescent glass layer, and the heat dissipation cover plate is arranged on the adhesive layer.
10. The laser color converter structure according to claim 9, characterized in that: A groove is provided on the upper surface of the heat dissipation substrate, and the fluorescent glass layer is filled in the groove. The thickness of the fluorescent glass layer is the same as the depth of the groove.
Citation Information
Patent Citations
High-power LED package structure and manufacturing method thereof
CN104124323A
Fluorescent glass sheet as well as preparation method and application thereof
CN114221207A
Light emitting device
JP2009141219A
Red light emitting module and preparation method therefor
WO2021093564A1
Cited By
Inorganic fluorescence conversion element for laser illumination and display as well as preparation and application of inorganic fluorescence conversion element
CN120320152A